BRIDGING PRIMARY CARE AND SURGERY: THE ROLE OF GENERAL PHYSICIANS AND ANESTHESIOLOGISTS IN PERIOPERATIVE OPTIMIZATION - Domi, Rudin; Kaci, Myzafer (Sanamed, 2025)
The transition of a patient from primary or internal medicine care to the operating room represents a critical juncture in perioperative management. Surgical patients requiring anesthesia must undergo thorough, multidisciplinary preparation involving family physicians, internists, hospitalists, anesthesiologists, surgeons, and physiotherapists. This multidimensional approach helps ensure a safe and seamless transition to anesthesia and surgery, thereby optimizing procedural outcomes. Key challenges during this phase include accurate assessment of physical status, risk stratification, optimization of comorbidities, and management of chronic medications. Adequate preoperative preparation minimizes the risk of surgical delays and enhances patient safety. This paper aims to highlight critical issues that can be addressed collaboratively by general physicians and anesthesiologists, fostering improved communication, shared knowledge, and clinical expertise.
Keywords: perioperative medicine; anesthesia; surgery; chronic medications; comorbidities; perioperative risk stratification